2017
DOI: 10.5194/bg-14-2387-2017
|View full text |Cite
|
Sign up to set email alerts
|

The European forest sector: past and future carbon budget and fluxes under different management scenarios

Abstract: Abstract. The comprehensive analysis of carbon stocks and fluxes of managed European forests is a prerequisite to quantify their role in biomass production and climate change mitigation. We applied the Carbon Budget Model (CBM) to 26 European countries, parameterized with country information on the historical forest age structure, management practices, harvest regimes and the main natural disturbances. We modeled the C stocks for the five forest pools plus harvested wood products (HWPs) and the fluxes among th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 44 publications
0
39
0
Order By: Relevance
“…They quantify the HWP sink at − 44.0 Mt CO 2 per year for the historical period 2000–2012 and forecast a decreasing trend until 2030 (− 22.9 Mt CO 2 per year). [26] show that the average amount of C in the European HWP pool is equal to 1843 Tg C for the period 2000–2012. In addition, they estimate that in 2030 the carbon stock changes in the EU forest pools (including HWPs) would reach a sink of 126 Tg C per year under the scenario assuming constant harvest and afforestation rates as in the aforementioned historical period.…”
Section: Introductionmentioning
confidence: 99%
“…They quantify the HWP sink at − 44.0 Mt CO 2 per year for the historical period 2000–2012 and forecast a decreasing trend until 2030 (− 22.9 Mt CO 2 per year). [26] show that the average amount of C in the European HWP pool is equal to 1843 Tg C for the period 2000–2012. In addition, they estimate that in 2030 the carbon stock changes in the EU forest pools (including HWPs) would reach a sink of 126 Tg C per year under the scenario assuming constant harvest and afforestation rates as in the aforementioned historical period.…”
Section: Introductionmentioning
confidence: 99%
“…Most EU Member States have up-to-date information from national forest inventories that can be used to meticulously define the state of the forest and the description of the current forest management practices, thereby providing an accurate estimate of the forest reference level. Such information is crucial for these types of modelling assessment as it has been shown that underlying assumptions concerning the initial age class distribution, management activities, growing conditions and historical natural disturbances influence the projected amount of harvest considerably, and as a consequence the future emissions and removals from managed forest land [21,26]. Further work on this subject would be useful not only to compare the outcome between models that are inherently different (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…With their NFI, most countries in Europe perform representative, regularly updated, long-term forest monitoring [9] that are used to parameterize and initialize empirical individual-tree growth models (e.g., [3,10]). Those models are representative over larger areas and allow to accurately project short-to mid-term forest resource development from the landscapes to national scale [3].…”
Section: Introductionmentioning
confidence: 99%